Zwrot korzyści majątkowej uzyskanej z przestępstwa skarbowego innej osoby w k.k.s. - Czwojda, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article presents the problem of reimbursement of financial benefit derived from a tax offense of another person in the Fiscal Penal Code. It examines the conditions for the application of financial benefits return in the Fiscal Penal Code but alsocomparison with the regulation included in the Penal Code. The article takes into account positive developments as well as contains criticism relating to certain solutions. As aresult, presented considerations point to the need to fill the normative gaps in such away that the forfeiture of financial benefits could be arational instrument of a fiscal penal policy.
Keywords: korzyści finansowe; zwrot korzyści finansowych